Penerapan Permainan Olahraga Tradisional Hadang untuk Meningkatkan Hasil Belajar Lari Cepat (Sprint) Siswa Kelas V SD - Muliadi Muliadi; Sitti Jauhar (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The purpose of this study was to describe the application of the traditional Hadang sports game to improve sprint learning outcomes for fifth grade students of SD Negeri 13 Biru, Tanete Riattang sub-district, Bone district. The results of this study are to be able to contribute to the improvement of physical education learning in sports and health (PJOK) in schools, and more specifically at the elementary school level. In particular, the expected benefit of this research is that it can be used as study material for improving the quality of running learning and also as a reference for PJOK teachers in developing learning strategies. This research is categorized as classroom action research (CAR). The implementation is carried out starting from planning, action, observation/evaluation and reflection activities to obtain accurate information. The focus in this action research is to apply the traditional game of Hadang with the results of students learning to sprint. The research subjects were fifth grade students of SD Negeri 13 Biru. The data collection techniques in this study were Observation and 60-meter sprint test. Data analysis techniques were data reduction, data presentation, and conclusion drawing. The results showed that the application of the traditional Hadang sports game could improve the sprint learning outcomes of the fifth grade students of SD Negeri 13 Biru. This is evidenced by an increase in the results of learning to run fast before being given an action with a low category/score increasing to a high category.